Learn to paint people quickly - Soan, Hazel (London : Batsford, 2017)
"From intimate portraits to bustling crowds, this practical guide by bestselling artist Hazel Soan teaches budding painters how to paint people . . . in just a few hours!"--provided by Amazon.com.
Easy-to-follow instructions, accompanied by inspiring paintings, mean you can gain confidence quickly in this compelling subject and be painting your own artworks in an afternoon.--Back cover.
-- Understanding the essentials -- Proportions -- The pose -- Lighting -- Clothing -- Figures in setting -- Portraits -- Go for it.
Includes index.
Keywords: Portrait painting -- Technique; Figure painting -- Technique; Painting -- Technique; Painting -- Study and teaching; Human figure in art